Dendrophthoe pentandra (Mango Mistletoe) leaves modulate steroidogenic acute regulatory protein, aromatase, and estrogen receptor expression in aged mice - Lilik Indahwati; Linda Ratna Wati; Inmas Andi Sermoati; Kusworini Handono; Wibi Riawan (Faculty of Medicine, Universitas Trisakti, 2026)
BACKGROUNDOvarian aging is associated with impaired steroidogenesis and estrogen signaling, contributing to reproductive dysfunction. Dendrophthoe pentandra (Mango Mistletoe), a flavonoid-rich plant with antioxidant properties, has demonstrated anti-inflammatory and cytoprotective effects in experimental studies. However, its role in modulating the integration of ovarian steroidogenic and estrogen-responsive pathways during aging remains unclear. This study evaluated the effects of D. pentandra leaf extract on the expression of steroidogenic acute regulatory protein (StAR), aromatase (CYP19A1), estrogen receptor α (ERα), and ERβ in aged female mice. METHODSThis experimental study included 25 female mice: 5 young (8–12 weeks) and 20 aged (18–20 months). Animals were allocated to five groups (n=5 per group): young controls, aged controls, and three aged treatment groups receiving D. pentandra leaf extract at doses of 150, 300, and 600 mg/kg BW, respectively, for 30 days. Protein expression was evaluated using immunohistochemistry and analyzed using one-way ANOVA followed by Tukey HSD post hoc test. RESULTSAged mice exhibited significantly lower expression of StAR, aromatase, ERα, and ERβ compared with young controls. Administration of D. pentandra extract significantly increased expression of all evaluated markers in a dose-dependent manner (p<0.001). Post hoc analysis demonstrated significant restoration of steroidogenic and estrogen-signaling–related protein expression, particularly in the highest-dose group, where aromatase, ERα, and ERβ expression approached or exceeded levels observed in young controls. CONCLUSIOND. pentandra leaf extract restored key components of ovarian steroidogenesis and estrogen signaling in aged mice, suggesting potential phytoendocrine modulatory activity against age-related ovarian endocrine decline.